The impact of planting dates on the performance of soybean varieties [Glycine max (L.) Merr.] in the Nigerian Savannas - Eseigbe, O.B.; Kamara, A.; Miko, S.; Omoigui, L.O.; Solomon, R.; Adeleke, M.A.; Tofa, A.I.; Bebeley, J. (MDPI, 2024)
Increasing delays in the onset of the rainy season and extended dry spells in the Nigerian savannas are complicating the determination of optimal planting dates for rain-fed crops, which increases risks for farmers. This study evaluated the impact of planting dates on soybean [Glycine max (L.) Merr.] performance to identify optimal planting dates for different soybean varieties in two agroecological zones (AEZs) of Nigeria. The study involved six planting dates (15 June, 22 June, 29 June, 6 July, 13 July, and 20 July) and three soybean varieties (TGX-1835-10E, TGX-1951-3F, TGX-1904-6F). Results showed significant differences in growth and yield parameters based on location, variety, and planting date. In the Sudan savanna (SS), AEZ at BUK-Kano, optimal yields (>1500 kg ha−1) were achieved when planting TGX-1835-10E and TGX-1951-3F from 15 to 29 June and TGX-1904-6F on 15 June. Planting beyond 29 June reduces yields by 12–55% for TGX-1835-10E and 27–63% for TGX-1951-3F. For TGX-1904-6F, planting after 15 June reduces yields by 27–90%. In the Northern Guinea savanna (NGS) AEZ at Zaria, optimal yields (>1500 kg ha−1) were obtained when planting TGX-1835-10E and TGX-1951-3F from 15 June to 6 July, and TGX-1904-6F between 15 to 29 June. Delaying planting beyond these dates significantly reduced yields by 18–31% for TGX-1835-10E and 12–20% for TGX-1951-3F and 10–41% for TGX-1904-6F.